Smart Classrooms: Mengintegrasikan IoT dan AI untuk Pembelajaran yang Lebih Interaktif dan Terukur - Khoir, Qoidul (Universitas KH. Abdul Chalim Pacet Mojokerto, 2024)
This study examines the impact of integrating the Internet of Things (IoT) and Artificial Intelligence (AI) in Smart Classrooms on interactivity, personalization, and learning evaluation. Using a descriptive qualitative method, data were collected through in-depth interviews, participatory observation, and document analysis in schools implementing this technology. The findings show that IoT and AI enhance student and teacher interaction, enable personalized learning tailored to individual needs, and provide more measurable and data-driven evaluations. Although challenges in technology adaptation and data security were identified, this study affirms that Smart Classrooms have the potential to become a more effective and responsive model of future education, aligned with technological advancements in education. These findings are supported by relevant educational theories, such as Vygotsky’s social learning theory and Bloom’s data-driven evaluation. They are further reinforced by related literature demonstrating that these technologies can significantly enhance the quality of education.